(+)-/(−)-Prunomarin A and (+)-pestalactone B, three new isocoumarin derivatives from the endophytic fungus Phomopsis prunorum. (6th July 2021) - Zhang, Xue-Qing; Lu, Zhen-Hong; Xia, Gui-Ru; Song, Wen-Min; Guo, Zhi-Yong; Proksch, Peter
Graphical abstract: Highlights: Three pairs of isocoumarin enantiomers were isolated from Phomopsis prunorum. Compounds (±)-1 represented rare sulfoxide-containing isocoumarins in nature. Compounds (+)-3 and (+)-3 displayed strong phytotoxicity. Abstract: Three pairs of isocoumarin enantiomers, (±)-prunomarin A (1 ), (±)-pestalactone B (2 ), and (±)-3, including three new compounds, (+)-/(−)-1 and (+)-2, were isolated from the endophytic fungus Phomopsis prunorum (F4-3). These enantiomeric pairs were existed as partial racemates and were achieved by chiral-HPLC separation. Their structures were elucidated by comprehensive spectroscopic data, X-ray diffraction, and ECD analysis. Compounds (±)-1 represented the first examples of naturally occurring sulfoxide-containing isocoumarin derivatives. Compound 1 showed anti-inflammatory activity for NO production with an IC50 value of 84.2 µM. Compounds (+)-/(−)-3 exhibited strong phytotoxicity against Amaranthus retroflexus .